Competence and educational role of family nurses in the care of patients with chronic kidney disease requiring renal replacement - Pluta, Agnieszka; Basińska-Drozd, Halina; Faleńczyk, Kamila; Budnik-Szymoniuk, Maria; Humańska, Marzena (Polish Journal of Public Health, 2013)
Family nurse is a nurse working in primary care, fulfilling the functions of the family, its members, the community, the environment they live in a situation of health, illness and disability. Nurse’s care includes patients in different stages of chronic kidney disease, including those requiring dialysis. At present, systematic increase in the number of patients included in the final stage of the disease, requiring renal replacement therapy is observed. Patient education in chronic kidney disease, especially renal replacement therapy requires an important part of his treatment. The purpose of this paper is to define the powers and the related role of family nurse education in the care of patients with chronic kidney disease requiring dialysis.